PENERAPAN KRIMINOLOGI SEBAGAI ILMU BANTU DALAM PENYIDIKAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK DI POLRES AGAM - Jukfa Hendriko; Fitriati Fitriati (UNES Journal of Swara Justisia, 2021)
The application of criminology in the investigation of criminal acts committed by children by investigators at the PPA Unit of the Satreskrim Polres Agam is used to make decisions for the settlement of crimes committed by children based on examinations of the children's motivation and reasons for committing crimes. The use of criminology in investigations shows several factors that cause children to commit crimes, namely because of the influence of friends or play groups such as in the crime of motorbike theft committed by children. Another cause is the negative influence of cellphones. For example, one case of intercourse with a child by a child in Agam District, the cause is because the child often watches pornographic videos. Constraints in the application of criminology in the investigation of criminal acts committed by children by investigators at the PPA Unit of the Criminal Investigation Unit of the Agam Police are the capabilities and methods of child assistant investigators / investigators in every process of investigating child criminal acts when it is related to the various kinds of education they get as well as with facilities and infrastructure and minimal funds.